Nanocompósito formado por ES-PANI e WO3.2H2O: análise das propriedades eletrônicas e da interação entre as fases através de técnicas experimentais e cálculos ab-initio - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The development of polymeric nanocomposites through the addition of inorganic particles is a way to improve their electrical and optical properties, as well as to propose new technological applications. Polyaniline (PANI) is one of the most studied polymers due to its ease of synthesis and adjustable conductivity. On the other hand, tungsten oxide (WO 3 ) and its hydrated phases, such as (WO 3 .2H 2 O), have been reported as important materials in photocatalysis and sensors. In this research, the WO 3 .2H 2 O phase was obtained during the in situ polymerization of ES-PANI in the presence of metallic tungsten (W) at synthesis times of 0.5, 1 and 2 h aiming the nanocomposite development. The nanocomposites were characterized using X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet-Visible (UV-Vis) and Complex Impedance Spectroscopy (CIS) techniques. The major phases of the nanocomposite ES-PANI/WO3.2H2O (PWO) were modeled via Density Functional Theory (DFT) in order to analyze their interactions and correlate these results with the data obtained experimentally. Two phases from the synthesis were detected by XRD, being WO3.2H2O and unpolymerized hydrochloride aniline. The diffraction patterns showed that after 2 h of synthesis, the metallic phase was totally converted into dihydrated oxide, and that the ANI-Hydrochloride phase presented low intensities of the diffraction peaks with the increase of the synthesis time, suggesting that the metallic phase inhibits the polymerization of the aniline monomer. The major phases observed in XRD patterns after 2 h of synthesis were used to model the theoretical structure PWO. The polymeric phase was deposited on a WO3.2H2O surface and, after geometric optimization, the phases interacted with each other at a distance of 0.60 A forming hydrogen bonds and strong attractive potential with charge transfer from the polymer to the oxide. The characteristic absorption bands of the nanocomposite phases were identified by FTIR, showing no change in the positions and modes of vibration of the isolated materials when in the form of nanocomposite, suggesting physical interactions between the phases. The UV-Vis analysis allowed to correlate the electronic phase transitions with charge transfer theoretically observed by the electronic density analysis. The electrical conductivity was calculated using CIS data, revealing that the nanocomposites obtained in 0.5, 1 and 2 h of synthesis presented conductivity of 1.4x10^(−1), 1.6x10^(−2) and 2.9x10^(−2) S.cm^(−1), respectively, showing that the nanocomposite formation improved the electronic conduction when compared to the pure ES-PANI. The conductive properties were confirmed by calculations of band structure, density of states and electric current: the polymer phase energy bands appeared in the middle of the oxide phase energy gap, enabling electronic transfer from the ES-PANI p orbitals to the d orbitals of WO3.2H2O. Furthermore, the electric current showed an Ohmic behavior typical of conductive materials, increasing linearly with the applied voltage.
Nanocomposite formed by ES-PANI and WO3.2H2O: analysis of the electronic properties and the interaction between phases by experimental techniques and ab-initio calculations
Keywords: Nanocompósitos (Materiais) - Análise; Materiais nanoestruturados - Análise; CIENCIAS EXATAS E DA TERRA: FISICA; Nanocompósito; Polianilina; Óxido de tungstênio; Condutividade elétrica; DFT